2023
DOI: 10.1038/s41598-023-49328-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of a curcumin nanoemulsion gel for the effective treatment of mycoses

Adel Al Fatease,
Ali Alqahtani,
Barkat A. Khan
et al.

Abstract: Fungal infections of skin including mycoses are one of the most common infections in skin or skins. Mycosis is caused by dermatophytes, non-dermatophyte moulds and yeasts. Various studies show different drugs to treat mycoses, yet there is need to treat it with applied drugs delivery. This study was designed to prepare a bio curcumin (CMN) nanoemulsion (CMN-NEs) for transdermal administration to treat mycoses. The self-nanoemulsification approach was used to prepare a nanoemulsion (NE), utilizing an oil phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The aim of the next study was to prepare biocurcumin (CMN) nanoemulsion (CMN-NE) for transdermal administration in the treatment of mycoses. It was shown that the prepared CMN-NE improved bioavailability, with better skin penetration in patients with mycosis [109].…”
Section: Antifungal Activitymentioning
confidence: 99%
“…The aim of the next study was to prepare biocurcumin (CMN) nanoemulsion (CMN-NE) for transdermal administration in the treatment of mycoses. It was shown that the prepared CMN-NE improved bioavailability, with better skin penetration in patients with mycosis [109].…”
Section: Antifungal Activitymentioning
confidence: 99%
“…The receptor compartment consists of 200 mL of pH 7.4 PBS taken in 250 mL beaker. The beaker was positioned over a magnetic stirrer, and 37 ± 0.5°C and 100 rpm were maintained as the study state constant [14]. At prede ned intervals (i.e., 0.25, 0.5, 0.75, 1, 2, 3, 4, 5, 6, 7 and 8 h), samples (1 mL) were removed and replaced with equivalent volumes of new PBS.…”
Section: In Vitro Release Studymentioning
confidence: 99%
“…The receptor compartment consists of 200 mL of pH 7.4 PBS taken in 250 mL beaker. The beaker was positioned over a magnetic stirrer, and 37 ± 0.5 °C and 100 rpm were maintained as the study state constant 15 . At predefined intervals (i.e., 0.25, 0.5, 0.75, 1, 2, 3, 4, 5, 6, 7 and 8 h), samples (1 mL) were removed and replaced with equivalent volumes of new PBS.…”
Section: In Vitro Release Studymentioning
confidence: 99%